2017
DOI: 10.3892/etm.2017.4492
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide, a component of traditional Chinese medicine, inhibits muscle cell atrophy (cachexia) in an in vivo and in vitro rat model of chronic renal failure by activating the ubiquitin-proteasome pathway

Abstract: The present study aimed to determine the effect of Astragalus polysaccharide (APS) in an in vivo and in vitro rat model of muscle atrophy (cachexia) caused by chronic renal failure (CRF), along with the potential corresponding roles of atroglin-1 and the ubiquitin-proteasome pathway. A rat model of CRF was established using subtotal bilateral nephrectomy. It was observed by reverse transcription-quantitative polymerase chain reaction and western blot analysis that APS and the specific inhibitor of nuclear fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Additionally, a deeper analysis of the effects of TMZ during C2C12 differentition shows that the transcript levels of factors involved in myotube hypotrophy, namely atrogin-1/MAFbx and myostatin, decrease in TMZ-treated C2C12 myoblasts cultured in DM for 24h, to progressively return to control levels at 48h and 72h (Figure 4E ), while MuRF-1 mRNA levels are not affected by TMZ in the same conditions (Figure 4E ). We speculate that, since TMZ inhibits NF-kB [ 53 , 54 ] which is related to Atrogin expression, this might cause a reduction of Atrogin [ 55 ]. However, this point needs to be elucidated by additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a deeper analysis of the effects of TMZ during C2C12 differentition shows that the transcript levels of factors involved in myotube hypotrophy, namely atrogin-1/MAFbx and myostatin, decrease in TMZ-treated C2C12 myoblasts cultured in DM for 24h, to progressively return to control levels at 48h and 72h (Figure 4E ), while MuRF-1 mRNA levels are not affected by TMZ in the same conditions (Figure 4E ). We speculate that, since TMZ inhibits NF-kB [ 53 , 54 ] which is related to Atrogin expression, this might cause a reduction of Atrogin [ 55 ]. However, this point needs to be elucidated by additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…CRF is considered as one of the most significant public health problems, with accumulating rates of occurrence and development [3]. There are about 10% of the general adult population affected by CRF worldwide, which is often complicated by sepsis and cardiovascular disease [4]. Previous study has revealed that CRF is characterized by slowly progressive chronic renal interstitial fibrosis (RIF) and accompanied with increased oxidative stress (OS) that is already found in the early stage of renal disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, JPYS decoction not only inhibited FoxO3a activation and ubiquitin-proteasome system (UPS), but also increased Cox IV, NRF-1, and PGC-1 α [25]. Atrogin-1 and MuRF-1 were also measured in the study by Geng Z et al, and astragalus polysaccharide significantly reduced the expression of atrogin-1 and ubiquitin in rat skeletal muscle [38].…”
Section: Resultsmentioning
confidence: 99%